Government Regulations, Interpreneurial Orientation and Stakeholder Network Capability in Achieving Organizational Performance - Rahmayandi Mulda (Newinera Publisher, 2020)
The purpose of this study is to analyze government and stakeholder regulations as well as entrepreneurial orientation in achieving organizational performance, this study to measure the impact of the institutional environment as government regulations and managerial ability in maintaining the relationship between stakeholder networks and entrepreneurial orientation in the context of industrial estates in Batam.The results of data analysis from industrial companies in Batam and its surroundings show that the maritime industry in Batam is entrepreneurially oriented and is significantly influenced by government policies as reflected in legal certainty and bureaucratic attitudes that help implement these policies.Besides, it is evident that the ability of management to establish relationships with many stakeholders, which consists of all existing partners and employees, also affects the growth of entrepreneurial orientation. The performance of the maritime industry in Batam is proven to be significantly influenced by entrepreneurial orientation directly.